Shwachman syndrome associated with de novo reciprocal translocation t(6;12)(q16.2;q21.2). Issue 11 (November 1995) - Masuno, M; Imaizumi, K; Nishimura, G; Nakamura, M; Saito, I; Akagi, K; Kuroki, Y
Abstract : We describe a de novo apparently balanced reciprocal translocation t(6;12)(q16.2; q21.2) in an 18 month old girl with Shwachman syndrome, characterised by exocrine pancreatic insufficiency and bone marrow dysfunction. The cause of this syndrome is unknown, although autosomal recessive inheritance has been proposed. The translocation breakpoints in the present patient may be candidate regions for a gene responsible for Shwachman syndrome.